Axial Compressive Strength of Foamcrete with Different Profiles and Dimensions - Othuman Mydin, M.A.; Sudin, M.A.S.; Md Sani, N. (EDP Sciences, 2014)
Lightweight foamcrete is a versatile material; primarily consist of a cement based mortar mixed with at least 20% volume of air. High flow ability, lower self-weight, minimal requirement of aggregate, controlled low strength and good thermal insulation properties are a few characteristics of foamcrete. Its dry densities, typically, is below 1600 kg/m3 with compressive strengths maximum of 15MPa. The ASTM standard provision specifies a correction factor for concrete strengths of between 14 and 42MPa to compensate for the reduced strength when the aspect height-to-diameter ratio of specimen is less than 2.0, while the CEB-FIP provision specifically mentions the ratio of 150 x 300 mm cylinder strength to 150 mm cube strength. However, both provisions requirements do not specifically clarify the applicability and/or modification of the correction factors for the compressive strength of foamcrete. This proposed laboratory work is intended to study the effect of different dimensions and profiles on the axial compressive strength of concrete. Specimens of various dimensions and profiles are cast with square and circular cross-sections i.e., cubes, prisms and cylinders, and to investigate their behavior in compression strength at 7 and 28 days. Hypothetically, compressive strength will decrease with the increase of concrete specimen dimension and concrete specimen with cube profile would yield comparable compressive strength to cylinder (100 x 100 x 100mm cube to 100dia x 200mm cylinder).